2008
DOI: 10.1097/yic.0b013e3282fcff2f
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled study of extract of ginkgo biloba added to clozapine in patients with treatment-resistant schizophrenia

Abstract: The focus of this study was the systematic evaluation of the clinical effects of the extract of ginkgo biloba (EGb) as an adjunct to the atypical antipsychotic clozapine in the treatment of refractory schizophrenia. In a placebo-controlled study, 42 patients with chronic, treatment-resistant schizophrenia, who were maintained on optimal doses of clozapine, were administered either 120 mg/day of EGb (N=20) or placebo (N=22) for 12 weeks. Clinical evaluations with the Brief Psychiatric Rating Scale, the Scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…It has been found that Ginkgo biloba (Gb) has antioxidant properties as a free radical scavenger (Marcocci et al, 1994;McKenna et al, 2001) and has been used to treat patients with schizophrenia usually as an assistant therapy on the basis of the typical (Knable, 2002; or atypical (Doruk et al, 2008) antipsychotic medication, especially in the chronic and/or treatment-resistant patients (Zhang et al, 2001a;Knable, 2002;Doruk et al, 2008). The primary results of these studies were usually comfortable but regrettably, they were still scattered in our opinion.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…It has been found that Ginkgo biloba (Gb) has antioxidant properties as a free radical scavenger (Marcocci et al, 1994;McKenna et al, 2001) and has been used to treat patients with schizophrenia usually as an assistant therapy on the basis of the typical (Knable, 2002; or atypical (Doruk et al, 2008) antipsychotic medication, especially in the chronic and/or treatment-resistant patients (Zhang et al, 2001a;Knable, 2002;Doruk et al, 2008). The primary results of these studies were usually comfortable but regrettably, they were still scattered in our opinion.…”
Section: Introductionmentioning
confidence: 79%
“…That is early recorded in the notable medicine monograph named "Shen Nong Ben Cao Jing" (Shen Nong's Herbal Classic), an earliest book on materia medica in China, appeared almost more than 2500 years ago. Nowadays, substantial scientific evidence has accumulated to find out that EGb protects against some kinds of neural and vascular damage (Diamond et al, 2000;Maclennan et al, 2002), like cerebral insufficiency , Alzheimer's disease (Le Bars et al, 2002;Smith and Luo, 2003;Andrieu et al, 2008), schizophrenia (Zhang et al, 2001a;Knable, 2002;Maclennan et al, 2002;Doruk et al, 2008). Studies of EGb on schizophrenia treatment were carried out in many countries (McKenna et al, 2001;, especially in China (Zhang et al, 2001a;.…”
Section: Discussionmentioning
confidence: 97%
“…Out of 14 search results, eight (Atmaca et al 2005;Doruk et al 2008;Lin et al 2007;Luo et al 1997;Zhang et al 2001Zhang et al a, b, 2006bZhou et al 1999) came from the PubMed database, three (Knable, 2002;Werneke, 2008;Werneke et al 2006) from other electronic databases, and three (Chen et al 1997;Meng et al 1996;Xu et al 2002) from crossreferencing of the electronically searched articles. Out of these, one was a case report (Lin et al 2007), one (Zhang et al 2006b) was unrelated to the subject matter, and three (Knable, 2002;Werneke, 2008;Werneke et al 2006) were review publications.…”
Section: Study Selectionmentioning
confidence: 98%
“…In addition, there are studies showing the efficacy of adjunctive treatment with some antioxidants. It has been found that add-on therapies with ginkgo biloba (Atmaca et al, 2005;Doruk et al, 2008;Zhang et al, 2001a,b), melatonin (Anderson and Maes, 2012), vitamins C and E (Reddy, 2011), N-acetylcysteine (Berk et al, 2013;Dean et al, 2011) and polyunsaturated fatty acids (Das, 2013) might be beneficial in terms of alleviating positive and negative symptoms, cognitive deficits, circadian rhythm disturbances and extrapyramidal symptoms.…”
Section: Therapeutic Implicationsmentioning
confidence: 97%